Binary Metal Single Atom Electrocatalysts with Synergistic Catalytic Activity toward High‐Rate and High Areal‐Capacity Lithium–Sulfur Batteries. (10th October 2022) - Ma, Lianbo; Qian, Ji; Li, Yongtao; Cheng, Yuwen; Wang, Shanying; Wang, Ziwei; Peng, Cheng; Wu, Konglin; Xu, Jie; Manke, Ingo; Yang, Chao; Adelhelm, Philipp; et al.
Abstract: Lithium–sulfur (Li–S) batteries with high theoretical energy density have been long considered as an alternative energy storage device to lithium‐ion batteries. Nevertheless, the polysulfide shuttle effects trigger fast capacity decay and short battery lifespan, severely hampering their practical utilizations. Herein, an efficient electrocatalyst comprising of nitrogen (N)‐coordinated binary metal single atoms (SAs) implanted within a hierarchical porous carbon skeleton (Fe/CoNHPC) is constructed to trap and catalyze polysulfides conversion through a separator coating strategy. It is demonstrated that the introduction of Co atom can enrich the electron number of Fe active center, thereby realizing the distinct synergistic catalytic effect of binary metal SAs and improving the bidirectional catalysis of Li–S redox reaction. As a result, Li–S batteries with the Fe/CoNHPC‐modified separator exhibit outstanding rate capability (740 mAh g −1 at 5.0 C), and superior long‐term cyclic stability (694 mAh g −1 after 600 cycles at 1.0 C). Increasing the sulfur loading to 4.8 mg cm −2, a remarkable areal capacity of 6.13 mAh cm −2 is achieved. Furthermore, in situ X‐ray diffraction and theoretical simulation results verify the catalysis mechanism of binary metal SAs by changing the rate‐determining steps, providing new directions for constructing high‐performance Li–S batteries. Abstract : Nitrogen‐coordinated binary metal single atoms (SAs) implanted within carbon skeleton are constructed as a high‐efficient electrocatalyst for Li–S batteries. Benefiting from the synergistic catalytic activity of binary metal SAs, the resultant Li–S batteries exhibit high specific capacity, great rate capability, and remarkable areal capacity under both low and high areal sulfur loadings.